PENGARUH FINANCIAL LEVERAGE DAN PERTUMBUHAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS (Studi Kasus pada Perusahaan Sub Sektor Kimia yang Terdaftar di Bursa Efek Indonesia) - Septiawanti, Serli; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study is to test partially and simultaneously the effect of financial leverage and company growth on financial pressures. Where the independent variable in this study is financial leverage and company growth, while the dependent variable is financial distress. This study used 9 chemical sub-sector companies listed on the Indonesia Stock Exchange in the 2013-2017 period, with the determination of samples using the purposive sampling method. The data in this study uses secondary data from the company's financial statements. Data analysis using simple and multiple linear regression analysis, t test, F test, and test coefficient of determination using SPSS 23 software. The results of this study indicate that the financial leverage variable partially (t test) has an effect on financial distress, the company's growth partially (t test) has an effect on financial distress in the chemical sub-sector companies listed on the Indonesia Stock Exchange. The test results (F) show that there is an influence between financial leverage and company growth on financial distress in the chemical sub-sector companies listed on the Indonesia Stock Exchange.Â Â Keywords: Financial Leverage, Company Growth, Financial Distress